Costa Rica's Development : From Good to Better - Oviedo, Ana Maria; Sanchez, Susana M.; Lindert, Kathy A.; Lopez, J. Humberto (World Bank, Washington, DC, 2015)
Costa Rica stands out for being among the most politically stable, progressive, prosperous, and environmentally conscious nations in the Latin America and the Caribbean region. Its development model has brought important economic, social, and environmental dividends, with sustained growth, upward mobility for a large share of the population, important gains in social indicators, and significant achievements in reforestation and conservation. However, there are a number of development challenges that need to be addressed to maintain the country’s successful development path. This Systematic Country Diagnostic takes stock of the poverty, inequality, and growth trends, addressing the following questions: To what extent has the Costa Rican development model been inclusive? What has driven growth in Costa Rica in recent years, and what are the bottlenecks that need to be addressed? How sustainable is the development model of Costa Rica economically, socially, and environmentally?